Physiological responses of Hiyung chili to different animal manures under acid sulfate soil conditions - MUHAMMAD HELMY ABDILLAH; MILA LUKMANA; LINDA RAHMAWATI; HERRY ISWAHYUDI; AMIRILIA INDAYATY; INDRIANI INDRIANI (Smujo International, 2026)
Abstract. Abdillah MH, Lukmana M, Rahmawati L, Iswahyudi H, Indayaty A, Indriani. 2026. Physiological responses of Hiyung chili to different animal manures under acid sulfate soil conditions. Asian J Agric 10 (1): g100109. https://doi.org/10.13057/asianjagric/g100109. Acid sulfate soils are marginal lands characterized by low pH, high saturation with Fe and Al, and poor nutrient availability. This study evaluated the effects of four types of animal manure-chicken, swiftlet, goat, and cattle-at five dosage levels (100-500 g) on Hiyung chili growth and yield, conducted from January to July 2024 at Politeknik Hasnur, South Kalimantan, Indonesia, using a Randomized Complete Block Design (RCBD) with 80 experimental units. Manures were composted aerobically, and dolomite was applied to plants. The data collected included plant height, leaf number, flower number, mature fruit count, fruit weight, and dry biomass, which were analyzed using ANOVA and DMRT at a 5% significance level. Chicken manure exhibited the most consistent and significant dose-response effects on the growth and yield of Hiyung chili pepper, with the 300 g dose increasing plant height, leaf number, flower number, fruit number, and fruit weight by approximately 30-60% compared to the lowest dose and showing significant differences from other manure types (DMRT 5%). In contrast, higher doses of cattle and swiftlet manure tended to reduce yield components by about 40-65%, indicating threshold effects and declining nutrient-use efficiency, with overall treatment effectiveness ranked as chicken manure > goat manure > swiftlet manure ≈ cattle manure. Chicken manure is recommended to improve Hiyung chili productivity on acid sulfate soils. This study highlights the role of local organic resources as sustainable inputs to improve soil fertility and crop productivity on acid sulfate soils, supporting long-term soil health and sustainable farming on marginal lands.